Tingkat Pengetahuan, Sikap Dan Tindakan Siswa-Siswi Kelas XI IPA Terhadap Kusta Di Sman I Kutalimbaru - Kalvin Tutamana Hutabarat; Eka Samuel P. Hutasoit (Universitas Methodist Indonesia, 2024)
Background: Leprosy is a disease caused by M.leprae, which has great affinity in nerve cells. Leprosy is still feared by the community, including some health workers. The dreaded thing of this leprosy disease is the disability caused by this disease. Indonesia is the third country in the world with most leprosy patients. While the city of Medan is the city with the most leprosy patients in the region of North Sumatra. Based on age distribution, most cases of leprosy occur in productive age and high school students are included in the productive age. This study aims to determine the level of knowledge, attitudes, and actions of students of class XI IPA SMA Negeri 1 Kutalimbaru about leprosy. Methods : This research is descriptive research with cross sectional approach. Performed at SMAN 1 Kutalimbaru. Data were taken from 57 samples of students selected by simple random sampling technique. From each sample, data were collected with questionnaires related to knowledge, attitudes and actions on leprosy. Results : Of the 57 people analyzed, 27 data were obtained with sufficient knowledge, 16 were knowledgeable, and 14 had less knowledge. For attitudes of respondents, most respondents have enough attitude, and for the actions of most respondents have enough action. Conclusion : the knowledge that the students of class XI IPA on leprosy is still included in the category enough, while for the attitude also included in the category enough and the act of entry in enough category.